2016
DOI: 10.2166/wst.2016.554
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lime addition during sewage sludge treatment on characteristics of resulting SSA when it is used in cementitious materials

Abstract: Final disposal of sewage sludge is important not only in terms of satisfying the regulations, but the aspect of choosing the optimal wastewater treatment technology, including the sludge treatment. In most EU countries, significant amounts of stabilized and dewatered sludge are incinerated, and sewage sludge ash (SSA) is generated as a by product. At the same time, lime is one of the commonly used additives in the sewage sludge treatment primarily to stabilize the sludge. In doing so, the question arose how de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In practice, most serious bottleneck is subsequent recycling of limed sludge. If it was incinerated, then lime pretreatment of sludge is unnecessary 12 . If it was bio-treated by aerobic compost or anaerobic digestion, the essential microbial groups had been inactivated by the heat released in lime stabilization and its strong alkalinity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, most serious bottleneck is subsequent recycling of limed sludge. If it was incinerated, then lime pretreatment of sludge is unnecessary 12 . If it was bio-treated by aerobic compost or anaerobic digestion, the essential microbial groups had been inactivated by the heat released in lime stabilization and its strong alkalinity.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent difficulty should be faced again that how to dispose lime stabilized sludge reasonably and how to choose its options among incineration, bio-treatment (such as aerobic compost) and landfill. The outlet of lime stabilized sludge seems to be some problems 2 , 11 , for instance, incremental results shown that if sludge incineration is accepted solution, but lime addition prior to incineration is unnecessary 12 . All the same, sludge lime treatment is widely used, particularly in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of Al, Ca, Si and Fe and pozzolanic properties, SSA can be applied in concrete production as a filler (replacement for fine aggregate) or as cement material. Vouk et al ( 2017 ) prepared mortars in which cement was replaced by SSA (10–20% fraction). They used ashes without lime and ashes where lime was added during stabilization or combustion of sewage sludge.…”
Section: Non-agricultural Directionsmentioning
confidence: 99%
“…Increasing the combustion temperature of sewage sludge is not recommended (up to 1000 °C) because the material’s mechanical properties deteriorate. Sludge conditioning with lime is also unnecessary because it does not significantly affect the quality of the material and causes nitrogen losses (Vouk et al 2017 ).…”
Section: Non-agricultural Directionsmentioning
confidence: 99%
“…Economic and environmental aspects confirm the advisability of research concerning the production of alternative materials with the use of sewage sludge [51]. 11. sewage sludge ash production of ceramics materials Suzuki et al [46] 12. sewage sludge production of lightweight clay ceramic Joan and Cecilia [27] 13. sewage sludge ash production of glass-ceramic material Zhikun et al [57] 14. waste paper sludge as an additive in the production of cement Karada and Awchar [29] 15. sewage sludge ash as an additive in the production of cement material Vouk et al [52] Characteristics of materials…”
Section: Application Of Sewage Sludge and Other Waste In A Constructimentioning
confidence: 99%